PERSPECTIVES ABOUT THE ANALYSIS OF ROMAN VITICULTURE IN GUADALQUIVIR ESTUARY. - Trapero Fernández, Pedro (Riparia, 2016)
The analysis of roman agriculture in the ancient stuary of Guadalquivir river, specially about viticulture, require a previous studies for determinate which could be the better places to plant vineyard, because of we don't know by the arqueology. Using a Geographical Information System (GIS) and the literary information of Columella, it is possible to do an approach to this knowledge, in the territory of Hasta Regia colony.